Antioxidant and anticancer activity of synthesized 4-amino-5-((aryl substituted)-4H-1, 2, 4-triazole-3-yl)thio-linked hydroxamic acid derivatives. (19th June 2019) - Das, Mousumi; Das, Bhaskar; Samanta, Amalesh
Abstract: Objectives: The antioxidant and anticancer activity of twelve 5-substituted-4-amino-1, 2, 4-triazole-linked hydroxamic acid derivatives were evaluated. Methods: Previously synthesized 2-((4-amino-5-substituted-4H-1, 2, 4-triazol-3-yl)thio)-N-hydroxyacetamide and 3-((4-amino-5-substituted-4H-1, 2, 4-triazol-3-yl)thio)-N-hydroxypropanamide (6a–6l ) were evaluated for in vitro antioxidant and in vivo anticancer activity. MDA-MB-231, MCF-7 and HCT 116 cell lines were used to evaluate IC50 values, in vitro. Ehrlich ascites carcinoma (EAC)-induced mice model was used to evaluate in vivo anticancer potential. Different biological markers were examined for drug-related toxicities. Key findings: Compound 6b revealed more potent antioxidant property among all tested compounds, even than the ascorbic acid. The IC50 values of compound 6b were found to be 5.71 ± 2.29 μg/ml (DPPH assay) and 4.12 ± 0.5 μg/ml (ABTS assay). Histopathology of liver sections of drug-treated mice was evaluated. Survival analysis showed that compound 6b could increase the life span as of the standard drug. Conclusions: After the assessment of all in vivo anticancer study related data, it was found that compound 6b possess superior anticancer potency in terms of efficacy and toxicity. From this experimental design, it could be concluded that further modification of this prototypical structure will lead to develop more potent antioxidant as well as an anticancer agent in the future.